Techno-economic analysis of parabolic trough solar thermal power plant for climate conditions of Pakistan - Asad Riaz (NUST201463527MCES64114F); Dr Muhammad Zubair (USPCAS-E, NUST, Islamabad, 2017)
TH-62
Keywords: MS-ESE Thesis MS Thesis